Factors associated with different smoking status in European adolescents: results of the SEYLE study - Banzer, Raphaela; Kaess, Michael; Brunner, Romuald (European child & adolescent psychiatry, 2017)
Early onset and long-term smoking are associated with physical and psychological health problems. The aim of the presented analysis was to investigate risk and influencing factors for different smoking status in a big sample of European adolescents. In the context of the “saving and empowering young lives in Europe” (SEYLE) study we surveyed 12,328 adolescents at the age of 13-17 from 11 countries. The survey took place in a school-based context using a questionnaire. Overall 58% reported the onset of ever-smoking under the age of 14 and 30.9% smoke on a daily basis. Multinomial logistic regression model showed significant positive associations between adolescent smoking and internalizing problems (suicidal behavior, direct self-injurious behavior, anxiety), externalizing problems (conduct problems, hyperactivity, substance consumption) and family problems (parental substance consumption, broken home). Our data show that smoking among adolescents is still a major public health problem and adolescents who smoke are at higher risk for mental problems. Further, adolescent smoking is associated with broken home families and parental behaviors. Therefore, early preventive measures are necessary not only for adolescents, but also for their parents.
Gesehen am 18.09.2018